To the problem of modern church dissidence on Ukraine: geopolitical aspect - Andrey V. Ishin (Проблемы постсоветского пространства)
The problem of church dissidence on Ukraine in focus of geopolitical processes is examined in the article. An author marks that confessional constituent of the armed capture of statepower with subsequent escalation of the armed opposition on the southeast of Ukraine — resultof introduction carefully thought out and long-term strategem of geopolitics of the West. Thusfragmentation of space of the Russian world, non-admission of political, economic and cultural co-operation of east slavs people, etnokonfessional «cleaning» of Ukrainian space with thesubsequent converting of Ukraine into a colonial-buffer area between the West and Russia, area,which will be frankly hostile the Russian world and will be controlled euro-atlantic structurescomes forward a primary objective. In a fight against canonical Orthodoxy on Ukraine the geopolitical opponents of the Russian world are involve the followings mechanisms: unprecedentedpolitical pressure, to the repression in regard to the adherents of Moscow Patriarchy, creation ofatmosphere of fear and religious intolerance; numerous destructions of orthodox temples duringa punitive operation on a southeast, power captures by the extremists of orthodox cult buildingswestering, in a center and on east of Ukraine; forcing at direct support of government of Ukraineof processes on creation of independent «pomestnoy church» with uttery nationalistic ideology;attempts of incorporation in the number of orthodox svyaschennosluzhiteley of Ukrainian Orthodox Church of Moscow Patriarchy of supporters of conception of religious championship ofKiev and historical seniority of the Ukrainian people in relation to Russian. An author comes tothe conclusion, that presently on Ukraine and on the whole in an international association thepeople of healthy will, representatives of all traditional confessions in defence of sound titles andfreedoms of believers, must unite.